Value transmission in two cultural traditions: a comparative study of an Islamic School and a Chinese School in Kuala Lumpur - Wong, Suk Ting Aida (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2013)
This thesis presents a comparative analysis of a private Islamic school and an independent Chinese school in Malaysia and examinesthe significance of tradition in the education process. Itstudies the transmission of traditional worldviews and values in the school setting at three levels, namely, the philosophy of education, curriculum and textbooks. It further explores whether the schools emphasize the contemporary thought of their traditions, and highlight the multi-cultural nature of Malaysian society as well as the importance of mutual respect and understanding between cultures. The thesis reveals that although both schools lay claim to tradition in their educational systems, they differ in the extent to which they rely on their traditions. While the Islamic school single-mindedly builds its education on the foundation of the Islamic faith, the Chinese school implements Confucian and Western thought on education as well as the national concern for economic development. The findings show that both schools rely on traditional values to nurture moral human beings and cultivate the love for learning. It is spirituality that distinguishes the two schools most. While the Islamic school adheres faithfully to the Islamic worldview, the Chinese school appears to have shifted from the traditional Heaven-consciousness of Confucianism to the modern, atheist outlook. With regard to Malaysian society, it is found that the Chinese school has attempted to highlight the country's multiculturalism and promote the idea of mutual respect and understanding among cultures, whereas the Islamic school does not appear to have cultivated such consciousness in their students. The thesis recommends that the two schools devise programs which will enable their students to have cross-cultural experiences. The thesis also recommends that the Islamic school improve its History textbooks so as to equip its students with a comprehensive understanding of Islamic History and Malaysian society.